The Strategic Impact of Project Management and Kanban in Enhancing Data Analysis Efficiency - Pratik Dahule (The Eastasouth Journal of Information System and Computer Science, 2023)
In data analysis projects, effective project management is critical to ensuring timely execution, resource optimization, and quality deliverables. This paper explores the integration of project management principles with the Kanban methodology to enhance workflow efficiency, task prioritization, and cross-functional collaboration. By providing a structured yet flexible approach, Kanban enables teams to visualize processes, limit work in progress, and mitigate bottlenecks. A case study from a utility company illustrates the practical application of Kanban, highlighting its impact on improving operational efficiency, reducing resolution times, and increasing customer satisfaction. Through data-driven techniques such as cohort analysis and sentiment analysis, the study evaluates internal performance improvements and shifts in customer perception. The findings demonstrate that Kanban, when coupled with data-driven decision-making, can significantly enhance project execution and service quality in data-intensive environments. This paper contributes to the growing body of research on agile project management strategies for data analysis initiatives.